Anterior inferior cerebellar artery loop and tinnitus—is there any association between them? - Saraf, Aditiya; Gupta, Nitika; Manhas, Monica; Kalsotra, Parmod (The Egyptian journal of otolaryngology, 2022)
Background Where there is no identifiable cause of otologic symptoms like hearing loss and tinnitus, it is believed that etiology could possibly involve a vascular loop in AICA compressing the vestibulo-cochlear nerve within the internal auditory canal. In this study, we aim to evaluate whether there is any association of AICA vascular loops with unexplained tinnitus. Methods The present prospective study was conducted in the Department of ENT, SMGS Hospital, GMC Jammu, from October 2020 to March 2022 on 131 subjects with unexplained tinnitus. All subjects were subjected to contrast enhanced MRI brain (3D fast spin echo T2W1 with drive equilibrium pulse) for evaluation of AICA using Chavda classification—type 1 (lying in CP angle, but not entering IAC), type 2 (entering IAC but extending < 50% of length of IAC), and type 3 (extending > 50% of length of IAC). Results Out of 131 unexplained tinnitus cases, 76 patients (58%) had AICA loop on MRI. Out of 16 patients with right sided tinnitus, 11 patients had AICA on same side, while 5 patients had AICA on the opposite (left) side. Out of 26 patients with left-sided tinnitus, 12 patients had AICA on same side, while 14 patients had AICA on the opposite (right) side, these findings being statistically insignificant ( p = 0.153). Conclusion From our study, we can conclude that the presence of AICA vascular loop either on CP angle or within IAC in tinnitus patients is an incidental finding and has no role in its etiology.